INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE «ENDOSCOPIC SURGERY IN GYNECOLOGY AND REPRODUCTIVE MEDICINE» : International Experience and Development Perspectives - Shukurov, F.I.; Sattarova, K.A.; Razzakova, N.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
The conference materials present data on the application of endoscopic technologies in the diagnosis and treatment of diseases of the reproductive system. Modern possibilities of using visualization methods, endoscopy, and genetic markers in the diagnosis of gynecological diseases are discussed. The principles of endoscopic treatment for all types of gynaecological pathology, including benign and malignant diseases, in women of reproductive age, using minimally invasive techniques are reflected. Current data on the features of management strategies before and after IVF are presented. Various approaches to solving problems of gynaecological pathologies and infertility issues are proposed. New data on the application of modern technologies in assisted reproductive technology programs are outlined. This material is intended for obstetricians-gynaecologists, reproductive specialists, researchers, and educators in medical institutions.